141k views
4 votes

√(3) x - 2 = {4}^(2)


User Cacheflowe
by
4.5k points

1 Answer

4 votes

Answer:


x=6*√(3)

Explanation:

Given:


√(3)x -2=4^(2)

To Find:

x =?

Solution:

We have,


√(3)x -2=4^(2)\\\\√(3)x -2=16\\\\√(3)x=16+2\\\\√(3)x =18\\\\x=(18)/(√(3) )

As square root of 3 is in denominator we will rationalize the denominator i.e multiply and divide by square root 3,so we get


\therefore x = (18)/(√(3) )* (√(3) )/(√(3) ) \\ \\\therefore x=(18)/(3)* √(3)\\\\\therefore x=6√(3)

∴ x = 6√3 is the final answer.

User RobStallion
by
6.5k points